1990
DOI: 10.3109/10408449009029331
|View full text |Cite
|
Sign up to set email alerts
|

Critical Reviews in: Carcinogenicity of Polyhalogenated Biphenyls: PCBs and PBBs

Abstract: Polychlorinated biphenyls (PCBs) and polybrominated biphenyls (PBBs) are compounds whose physical/chemical properties led to their widespread commercial use. Although their production has been banned or severely limited in most countries since the 1970s, the persistence and stability of these compounds have resulted in a worldwide distribution, especially of PCBs. PBB contamination is limited principally to the state of Michigan, where a series of tragic errors eventually resulted in the accumulation of residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
208
0
3

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 323 publications
(215 citation statements)
references
References 196 publications
4
208
0
3
Order By: Relevance
“…The relative risks in these four studies are in the same range as those estimated from the animal data (16,17). The potential association with ER status is of some interest, given the estrogenic activity of DDT and the rising rates of ER-positive cancer among older women (18).…”
supporting
confidence: 59%
“…The relative risks in these four studies are in the same range as those estimated from the animal data (16,17). The potential association with ER status is of some interest, given the estrogenic activity of DDT and the rising rates of ER-positive cancer among older women (18).…”
supporting
confidence: 59%
“…A number of carcinogenic mechanisms [127], including formation of reactive oxygen species [69,145,157], endocrine disruption [80,180,204], and immune compromise [50,147,162,173,174,209,219], are known to be activated by PCBs. The evidence that PCBs can cause immune suppression is of particular interest because melanoma risk is known to increase between threefold and fourfold in individuals who are immunosuppressed due to agents given for organ transplantation [104,117,138].…”
Section: Pcbsmentioning
confidence: 99%
“…They activate specific receptors, such as the Ah receptor and the constitutive androstane receptor (CAR), and induce the specific cytochrome P-450s that are activated by these receptors (Robertson and Hansen 2001). PCB mixtures have been shown to be carcinogenic in the liver (Silberhorn et al 1990). In addition, many PCB congeners have been demonstrated to have promoting activity; studies have found them to increase the formation of both tumors and altered hepatic foci (Glauert et al 2001).…”
Section: Introductionmentioning
confidence: 99%